Hydatic cyst prevalence in slaughtered animals, A neglected health problem - Rostami Nejad, Mohamamd; Jahani-Sherafat, Somayeh; Cheraghipour, Kourosh; Nazemallhoseini Mojarad, Ehsan; Taghipour, Nilofar; Zali, Mohammad Reza (Archives of Advances in Biosciences, 2012)
Lorestan and other part of Iran are one of the important endemic focuses for the major zoonotic parasitic diseases like cystic hydatid disease where several species of intermediate host are commonly infected with Echinococcus granulosus. Meat inspection records in a slaughtered house were used to determine the prevalence of Hydatidosis in sheep, cattle, and goats in Lorestan province (Aleshtar) located in South-West of Iran. The data were collected during a 5 year period from 2002 to 2006. A total of 40,431 animals (cattle 6993; sheep 14084; goats 19354) slaughtered in the 5-year period and overall 2885 (7.13%) lungs and 2885 (7.13%) livers and 1598 (3.95%) peritoneal cavity were contaminated by hydatid cyst. One thousand and eight hundred sixty eight (26.71%) out of 6993 of cattle, 2989/14084 (21.22%) of sheep and 2511/19354 (12.97%) of goats were infected by hydatid cyst in liver, lung and peritoneal cavity respectively. This study indicates that the highest prevalence of Hydatidosis was found in Aleshtar, Lorestan as compared to the rest of Iran (p<0.05). The annual prevalence of lung condemnations due to hydatidosis was increased from 8.3, 5 and 1.3% in Sep 2002 to Sep 2003 to 20.5, 8 and 5.5 % in Sep2005 to Sep2006 for cattle, sheep, and goats, respectively. An urgent attention is required to work on lack of awareness among farmers, lack of a policy to destroy the infected organs, prevention of access of dogs to raw offal’s and other responsible factors.Lorestan and other part of Iran are one of the important endemic focuses for the major zoonotic parasitic diseases like cystic hydatid disease where several species of intermediate host are commonly infected with Echinococcus granulosus. Meat inspection records in a slaughtered house were used to determine the prevalence of Hydatidosis in sheep, cattle, and goats in Lorestan province (Aleshtar) located in South-West of Iran. The data were collected during a 5 year period from 2002 to 2006. A total of 40,431 animals (cattle 6993; sheep 14084; goats 19354) slaughtered in the 5-year period and overall 2885 (7.13%) lungs and 2885 (7.13%) livers and 1598 (3.95%) peritoneal cavity were contaminated by hydatid cyst. One thousand and eight hundred sixty eight (26.71%) out of 6993 of cattle, 2989/14084 (21.22%) of sheep and 2511/19354 (12.97%) of goats were infected by hydatid cyst in liver, lung and peritoneal cavity respectively. This study indicates that the highest prevalence of Hydatidosis was found in Aleshtar, Lorestan as compared to the rest of Iran (p<0.05). The annual prevalence of lung condemnations due to hydatidosis was increased from 8.3, 5 and 1.3% in Sep 2002 to Sep 2003 to 20.5, 8 and 5.5 % in Sep2005 to Sep2006 for cattle, sheep, and goats, respectively. An urgent attention is required to work on lack of awareness among farmers, lack of a policy to destroy the infected organs, prevention of access of dogs to raw offal’s and other responsible factors.